AB1149 POOR RESPONSE TO HEPATITIS B VACCINATION IN RHEUMATIC PATIENTS TREATED WITH BIOLOGIC THERAPY – IMPLICATIONS FOR CLINICAL PRACTICE. (2nd June 2020) - Romão, V. C; Ávila-Ribeiro, P.; Gonçalves, M. J.; Cruz-Machado, A. R.; Guerreiro, A.; Teixeira, V.; Valido, A.; Silva-Dinis, J.; Vieira-Sousa, E.; Saavedra, M. J.; Leite, E.; Tato Marinho, R.; et al.
Abstract : Background: Hepatitis B virus (HBV) vaccination is recommended for rheumatic patients starting biologic therapy. There is some evidence that HBV vaccination is effective in patients under conventional disease modifying anti-rheumatic drugs (DMARDs), but it is currently unclear whether this also applies to biologics. Objectives: To assess the efficacy and safety of HBV vaccination in patients with rheumatic diseases treated with biologics. Methods: We included patients with any inflammatory rheumatic diseases treated with any biologic, who were negative for anti-HBs and anti-HBc and had never been vaccinated for HBV. Engerix B® was administered at 0, 1 and 6 months and anti-HBs was re-assessed ≥1 month after last dose. Response was defined as anti-HBs>10IU/L and compared against healthy controls (HC) undergoing Occupational Health immunization. Disease flare was evaluated before and until at least 1 month post-vaccination. We recorded serious adverse events (SAE) and immune-related disorders not previously present. Results: We included 67 patients, most treated with TNF inhibitors (TNFi), and 70 HC (Table 1 ). Most patients were taking concomitant DMARDs (69%) and were in remission/low disease activity (59%). Only 20 patients (30%) had a positive response to vaccination, in comparison to 68 HC (97%, p<0.001). Mean post-vaccination anti-HBs titre was significantly lower in responding patients than HC (569 ± 772 vs 1316 ± 811U/L, p<0.001). Responders diagnoses were RA (n=8 [25%]), PsA (n=7 [39%]), AS (n=4 [33%]) and IBD-associated SpA (n=1[100%]). Response was seen in 19/53 patients treated with TNFi (36%), but only 1/14 (7%) of patients treated with non-TNFi (p=0.037). Importantly, some responders had to temporarily interrupt biologic therapy due to other intercurrences for at least one administration. No clinical or demographic variables were associated with response, including age and disease activity. Fourteen patients (21%) experienced disease flares, of which 7 were mild and did not require therapy adjustment; 3 patients required minor treatment/dose adjustments; 4 patients had secondary failures that led to switches. There were 3 SAE (acute diverticulitis; abdominal infection; atrial fibrillation and urinary infection) 1-4 months after 1 st /2 nd dose, deemed not to be related to vaccination. One RA patient on infliximab had bilateral uveitis 2 months after the 1 st vaccine dose, which resolved with topical therapy. Conclusion: In this study, HBV vaccination response was poor and lower in rheumatic patients treated with biologic therapy than in healthy adults. Vaccination was overall safe but there were 4 severe flares and 3 SAE that lead to treatment switch/interruption, although causal association is difficult to establish. Our data reinforce the recommendation for HBV vaccination prior to starting biologic therapy, possibly even as soon as the diagnosis is established. Alternative HBV vaccination strategies should be investigated in patients already treated with biologics. Disclosure of Interests: Vasco C Romão: None declared, Pedro Ávila-Ribeiro Grant/research support from: Novartis, Maria João Gonçalves: None declared, Ana Rita Cruz-Machado: None declared, André Guerreiro: None declared, Vítor Teixeira: None declared, Ana Valido: None declared, Joana Silva-Dinis: None declared, Elsa Vieira-Sousa: None declared, Maria João Saavedra: None declared, Ema Leite: None declared, Rui Tato Marinho: None declared, Joao Eurico Fonseca: None declared